Karakteristik Petani Pemilik Penggarap Kelapa Di Desa Pinamorongan Kecamatan Tareran Kabupaten Minahasa Selatan - Pinatik, Luis; Ngangi, Charles Reijnaldo; Taroreh, Melissa Lady Gesela (Sam Ratulangi University, 2023)
This study aims to determine the characteristics of farmers who own coconut cultivators in Pinamorongan Village, Tareran District, South Minahasa Regency. This research was conducted during May-June 2022. In Pinamorongan Village, Tareran District, South Minahasa Regency, the data used in this study were primary data and secondary data. Primary data was obtained through interviews with coconut cultivators in Pinamorongan Village using a questionnaire. Meanwhile, secondary data was taken from the Pinamorongan Village Office and the Central Bureau of Statistics for South Minahasa Regency. The results showed that the highest age of the farmer who owned the coconut cultivator in Pinamorongan Village was 71 years old and the lowest was 39 years old. Based on the education level of farmers, the highest was SMA/SMK while the lowest was SD and did not go to school. Based on the experience of farming, the highest is 50 years and the lowest is 10 years. Based on the coconut land area, the highest is 3 hectares (ha) and the lowest is 1/2 hectare (ha). Based on the number of dependents of the farming family, the most is 4 people and the least is 1 person. Based on the income level of farmers, the highest is IDR 7,454,439/harvest and the lowest is IDR 246,276/harvest.